Efficacy of Two Estrus Synchronization Protocols in Crossbred Gyr Dairy Cows and Their Relationship with Heat Stress in the Peruvian Tropics - Vásquez Tarrillo, Ronald Will (2025)
The performance of estrus synchronization protocols may be influenced by stressful environmental conditions, even in tropically adapted cattle. This study evaluated the efficacy of two synchronization protocols for fixed-time artificial insemination (FTAI) in crossbred Gyr dairy cows and their relationship with heat stress under Peruvian tropical conditions. Multiparous lactating cows under semi-intensive systems were synchronized and divided into two groups: the conventional protocol (PC9) and the prolonged proestrus protocol (J-Synch6). Estrus manifestation, pregnancy rate, and their association with the temperature–humidity index (THI) were analyzed across seven phases of the FTAI program (73 days). In PC9 cows, no significant effect of the number of hours in each heat stress category according to THI was found. Conversely, in J-Synch6 cows, more hours in Category 0 (THI < 72) during Phases 1 to 4 (follicular emergence to preovulatory follicle) had a positive effect on the estrus manifestation, whereas in Phase 3 (follicular growth), higher exposure to Category 3 (THI ≥ 83) had a negative effect on estrus manifestation. Both protocols demonstrated similar estrus and pregnancy rates, although heat stress affected estrus rates in J-Synch6, but not pregnancy. The choice of protocol should account for heat stress risks during specific periods of the year to maximize success.